Analysis of Factors That Influence the Attractiveness of Muslim Students Using Online Loan Applications in Soloraya - Azhari, Nonik Rindi; Putri, Rizky Nur Ayuningtyas (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Today's technological advancements in the financial sector have given rise to several new ideas; among them, online loans are fintech-based. Online lending is a public financial solution that facilitates the provision of cheap, transparent, and efficient financial services. The purpose of this study is to examine the many elements that have an impact on the willingness of Muslim students in Soloraya who use online loan applications. The research method used is the quantitative method. Primary data was used in this study. The questionnaire was given to 96 respondents who were selected using purposive sampling using Lemeshow's algorithm. With data analysis using SPSS V.26 statistical assistance. The results of this study indicate that the variables of security, hedonic motivation, and loan disbursement speed have a significant effect, while the ease of use variable has no significant effect on the attractiveness of Muslim students in using online loan applications in Soloraya. Therefore, to decide to use online loan application services, fundamental factors are needed. However, ease of use is not fully a fundamental factor in attracting Muslim students to use online loan application services in Soloraya.